APPLICATION OF COBALT COATING BY BIPOLAR ELECTRONIC METHOD - Zayets, Danilo; Kuzevanova, Irina; Kovalenko, Irina; Vlasenko, Natalia; Zulfigarov, Artur; Shpak, Arsenii (Proceedings of National Aviation University (archive), 2020)
There were proposed an electrochemical method of obtaining a cobalt coating using a bipolar electrolyzer. The potential distribution at the bipolar electrode is more uniform than at the monopolar for others conditions that are the same. The combination of the uniformity with the optimal limit current gives us a try to get compact metal precipitates with microhardness, that is high enough, small crystalline and well-clutched with the base. The obtained results indicate the possibility of using a bipolar electrolyzer in practice for the application of cobalt on wire, and also using it as a protective is decorative.